2015
DOI: 10.1177/1045159515596928
|View full text |Cite
|
Sign up to set email alerts
|

Academic Learning Teams in Accelerated Adult Programs

Abstract: This article reports adult students’ (N = 632) perceptions of long-functioning academic learning teams in accelerated online and on-campus business cohort groups in six constructs: attraction to team, performance expectation alignment, workload distribution, intra-team conflict, preference for teamwork, and impact on learning. Comparisons between students in online and on-campus programs revealed, regardless of degree or delivery model, a majority of adult students preferred individual work and did not believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Favor and Kulp (2015) offered a different view of adult learning online. The authors, comparing students’ perceptions of learning teams in online and campus accelerated adult programs, while acknowledging that the study was conducted at only one institution, reported that online adult students were more likely to prefer individual work compared with campus students and believed that working in teams did not enhance their learning experience (Favor and Kulp, 2015).…”
Section: Core Beliefs Weaknesses and Implications For Adult Online Learningmentioning
confidence: 99%
“…Favor and Kulp (2015) offered a different view of adult learning online. The authors, comparing students’ perceptions of learning teams in online and campus accelerated adult programs, while acknowledging that the study was conducted at only one institution, reported that online adult students were more likely to prefer individual work compared with campus students and believed that working in teams did not enhance their learning experience (Favor and Kulp, 2015).…”
Section: Core Beliefs Weaknesses and Implications For Adult Online Learningmentioning
confidence: 99%
“…Examples of the second category of challenges are the nature of activities, the structure of activities, and the availability of scaffolding (Falcione et al, 2019;Han & Ellis, 2021;Tan et al, 2016). Student factors are the third category of challenges, including students' attitudes, emotions, self-efficacy, self-regulation, and metacognition (Han & Ellis, 2021;Favor & Kulp, 2015). Among all challenges, student factors might be the leading impediment to the success of collaborative learning.…”
Section: B Challenges In Implementing Collaborative Projectsmentioning
confidence: 99%
“…Without all team members' commitment to collaborative learning, the failure of learning could develop from ineffective communication, different discernments of quality work, the unequal contribution of efforts among team members, and the reluctance to accommodating multiple individuals' schedules (Busch et al, 2021;Butt, 2017). Additionally, some students voice anxiety and frustration because they work with teammates with different mindsets and goals or are less engaged in team-based activities (Busch et al, 2021;Favor & Kulp, 2015;Kima & Lim, 2018).…”
Section: B Challenges In Implementing Collaborative Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies present methods for designing optimal courses (Katzenstein et al, 1994;Dubas & Strong, 1993) or enhancing existing courses (Dubas et al, 2016) while others have offered guidelines for enhanced online discussion (Favor & Kulp, 2015) and rubrics for assessment of participation in online discussion (Hazari, 2004;Kayler & Weller, 2007;Alden, 2011).…”
mentioning
confidence: 99%